Integrated Interaction Between Tourism, Economy, and Ecology in Indonesia: Coupling Coordination Degree Method - Raudlatul Faizah; Deni Kusumawardani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
Indonesian tourism sector becomes an important part of national development planning over the past decade. However, the development of the tourism sector stimulates many negative ecological issues, such as garbage deposits, emissions, and other environmental degradation. Tourism has a complex relationship with the economy and ecological quality, so it is essential to investigate the progress of a tourism-economy-ecology system. An integrated study of the system can be analyzed using the coupling coordination degree method (CCDM). This method provides an overview of the interaction rate and the level of coordination in the systems over time. The findings show that the degree of coupling between tourism-economy-ecology systems increases from run-in to high phases. This condition indicates that there was a strong connection between the systems during the observation. Meanwhile, the degree of coupling coordination constitutes an ever-increasing evolution from approaching disorder to well coordination. It shows that the systems are increasingly supportive of each other. Conversely, the higher level of coordination is accompanied by a decline in the environmental system. Promoting ecological quality is a critical policy for sustainable tourism growth, and it demands more attention from all parties involved in the tourism industry.